ENDEMIC PLANT SPECIES OF IRAQ: FROM FLORISTIC DIVERSITY TO CRITICAL ANALYSIS REVIEW - YOUSSEF, SAMI (Journal of Duhok University, 2020)
The endemic flora is the heart of our understanding of the current biodiversity hotspots, and plays a critical role to conceive successful management strategies for global biodiversity conservation. In Iraq territory context, despite its high plant diversity value, the endemicity is still largely under-investigated and there is no updated database of the Iraqi endemic flora. Therefore, this study sets out to present an updated list of the endemic plant species in Iraq, including a quantitative analysis of their floristic analysis, biological life forms, and geographical distribution. This first Iraqi endemic list can be seen as the first step towards better understanding of the floristic diversity, and can play an important role for future conservation priorities. This endemic list was based initially on the classical flora of Iraq and it has been completed and refining according to the floras of the neighbouring countries. To establish an updated list, it has been added all the Iraqi endemic taxa newly described by retrieving it from the botanical papers and taxonomical websites. For each endemic taxa researcher has provided the following floristic baseline: scientific name, family, phytogeographical distribution, elevation range, biological life forms, and IUCN assessment. The results of this floristic investigation present for the first time an updated endemic list of Iraqi plant species which contains a total of 174 endemic taxa(153 species, 11 subspecies, 10 varieties) in 27 families and 75 genera. They represent an endemicity rate of 5.3% of the total estimated flora of Iraq, which constitutes a low level compared to those of neighboring Irano-Anatolian countries. The family Asteraceae, Papilionaceae, Boraginaceae and Apiaceae are the richest flowering families. The life biological forms indicate that a major part of endemic taxa are chamaephytes (44%) and perennial hemicryptophytes (32%) as an adaptation indicator to the dry-harsh environmental conditions of the Irano-Anatolian mountainous areas. These floristic quantitative analysis support the idea that the species richness and endemicity are not uniformly distributed within the altitudinal gradient and phytogeographical districts of Iraq. For instance, a significant part of the Iraqi endemic taxa concentrate on the Zagrosian foothills and the mountain range between 1000 and 1700. The most striking findings were that only one taxon on average per year was newly described for Iraq, over the last 20 years, compared to around 50 taxa for Iran and Turkey confirming its status of the floristic knowledge coldspot. The current findings add substantially to our understanding of the endemism diversity in Iraqi Zagrosian part, and can serve as a base for future floristic investigation and biodiversity conservation studies